Teo en el hipermercado - Capdevila, Juan.; Denou, Violeta (Barcelona : Timun Mas, 1900)
Teo and his mother go downtown to the market to shop. At the market, they find many kinds of foods, smells, and interesting things for sale.
Keywords: Markets -- Fiction; Shopping -- Fiction; Spanish language materials; Markets -- Fiction; Shopping -- Fiction; Spanish language